Pembinaan Pembelajaran Bahasa Arab dalam Mengembangkan Kemampuan Pemahaman Al-Qur’an Santri Tahfidzul Qur’an Al-Fajri Makassar - Besse Ruhaya (KHIDMAH: Jurnal Pengabdian Masyarakat, 2023)
The Qur'an was revealed to the Prophet Muhammad Saw using Arabic, and became the language of education, science, diplomacy, socioeconomic, and cultural transactions. The purpose of this devotion is to provide guidance for learning Arabic in understanding the Qur'an. The method used is a direct method in the skills of al-istima' and al-kitabah, the students listen directly to the material given and write down what has been listened to. The results showed that 20% of students can listen, 65% of students can write, and 15% students cannot listen and write properly and correctly. This shows that there is still a need for further guidance so that students can listen and write the Qur'an properly and correctly.